Implementation of the Tirta Coaching Model in the Development of Elementary School Teachers’ Professionalism - Budi Saputra; Syaiful Eddy; Djunaidi Djunaidi (Journal of Social Work and Science Education, 2027)
This study examines the implementation of the TIRTA Coaching model (Goal, Identification, Action Plan, Responsibility) in developing teacher professionalism at SD Negeri 1 Sumber Marga Telang, Banyuasin Regency, South Sumatra, within the context of Merdeka Curriculum implementation in a peripheral school setting. A phenomenological qualitative approach was employed to explore teachers’ lived experiences during coaching. Purposively selected informants included the principal, seven certified teachers, and a school supervisor. Primary data were gathered through in-depth interviews, passive participatory observation, and documentation, analyzed using Miles and Huberman’s interactive model, with validity ensured through source and technique triangulation. Findings reveal that the TIRTA model shifts supervision from evaluative to reflective-dialogic approaches, fostering trust and psychological safety. Teachers internalized professionalism as ongoing reflection, contextual innovation, and independent commitment. However, constraints included administrative burdens, limited facilities, and swamp geography challenges. This study provides contextualized evidence of the TIRTA model’s applicability in a geographically isolated Indonesian elementary school, an underrepresented setting in coaching literature. The model offers a replicable framework for school principals to conduct non-evaluative, empowering coaching that sustains teacher professional growth despite infrastructural limitations. This research contributes empirical insights that the TIRTA Coaching model effectively supports curriculum reform and teacher development in peripheral schools, demonstrating that relational, reflective coaching can overcome geographic and resource constraints to enhance professional practice and educational quality.